(untitled) (The International Journal for Scientific Research, 2025)
The verb is one of the three types of word, and it is important because it gives two semantic dimensions in a single sentence. It gives a lexical dimension that determines its conventional meaning, and a temporal dimension that determines the time in which the meaning of the verb occurred. It also has an important role in the actual sentence that it presides over, and it may be Part of the nominal sentence in some types of its predicate. This importance urges the study of this type, and this study is an attempt to establish some of its vocabulary, in which a verb was chosen that cannot give a diverse temporal meaning, but rather resides in one time that does not budge from it, which is the rigid verb. Importance of the Research: the importance of this research is as follows: - The importance of the subject studied, which is the inanimate form of verbs, and the impact resulting from the significance of the presence of this type of vocabulary in the language, as this study is considered an authentication of a type of Arabic vocabulary. - The diversity of vocabulary is often a reason for the diversity of meaning. In this case, in the case of the inanimate verb, we will look at the effect of the meaning on the vocabulary (verbs) specifically, which made them deprived of their characteristic of temporal diversity due to the diversity of form. Research Objective: This research seeks to root some of the language’s vocabulary. To determine the characteristics of this diversity of types of Arabic vocabulary. Research Methodology: The methodology of this research is based on describing, analyzing and evaluating the information found among the ancients and moderns about the inertia of action.